Analisis Perilaku Struktur Bangunan Rumah Metode RISHA dan RIKO Ditinjau Terhadap Gempa Linier Dinamik Respon Spektrum di Kabupaten Minahasa Selatan - Nico A Simanjuntak; Okta Meilawaty; Frieda (Jurnal Serambi Engineering, 2024)
Earthquakes are natural disasters that frequently occur in various regions of Indonesia, including South Minahasa Regency and North Sulawesi Province. This research was conducted to determine the structural behaviour of residential buildings using RISHA and RIKO methods in terms of dynamic linear earthquake load response spectrum based on base shear, displacement and floor drift. A quantitative research methodology was used in this study. The project started with a literature review, data collection and structural modelling using the ETABS program. The basic shear force on the Z axis for the RISHA method house is 376,943 kN and for the RIKO method house it is 294,896 kN, according to the analytical results. For the RISHA method house, the maximum displacement value in the x-direction is 3,639 mm and in the y-direction is 2,791 mm, and for the RIKO method house, it is 21,741 mm in the x-direction and 21,976 mm in the y-direction. According to SNI-1726-2019, the story drift that occurs in the RIHA method house structure meets the requirements because its value is less than the ultimate limit of the story drift value of 60 mm. On the other hand, the story drift occurring in the RIKO method house structure does not meet the requirements because its value is greater than the ultimate limit of the story drift value of 60 mm